A case study of the socio-economic conditions of a factory in Johor / Lim Lay Kheng - Lim , Lay Kheng (1985)
This graduation exercise tries to look at the process of industrialization by focusing on events at factory level. This is a case-study of a manufacturing company, comparing the socio-economic conditions of its two factories and its workers. Based on observations and interviews, this study first tries to give a comprehensive picture of production process, capitalization, the research methodology and the organizational structure. Secondly, it deals with the labour force and company policies which determine the conditions of work for the workers. How the workers perceive their work is also dealt with. The differences in behavior and attitude of groups of workers are shown to be related to their races, age, sex, income level, educational level, etc. The area of labour-management relationship in one of the factories is also covered, showing the development of the trade union and its activities as well as the problems faced in the relationship between the two parties involved in production.